2017
DOI: 10.1111/jace.15214
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a ceria‐based anode functional layer with a stabilized zirconia electrolyte: Considerations from a materials perspective

Abstract: We report on the materials interaction of gadolinium doped ceria (GDC) and yttria stabilized zirconia (YSZ) in the context of high temperature sintering during manufacturing of anode supported solid oxide fuel cells (AS-SOFC). While ceria-based anodes are expected to show superior electrochemical performance and enhanced sulfur and coking tolerance in comparison to zirconia-based anodes, we demonstrate that the incorporation of a Ni-GDC anode into an ASC with YSZ electrolyte decreases the performance of the AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Although the addition of LW reduced the specific surface area of the anode, LW showed a better stabilizing effect than that of WO 3 because the specific surface area was almost unchanged after the reoxidation processes, whereas the surface areas of Ni‐YSZ and Ni‐YSZ‐0.42 wt % WO 3 decreased by 53 and 40 %, respectively, after the redox treatment. The elemental contents of the sample surfaces can be semiquantitatively measured by X‐ray photoelectron spectroscopy (XPS) . As shown in Table S1 in the Supporting Information, the atomic ratios of Ni metal were 56.3, 45.0, and 34.0 % for unmodified and 2 and 5 wt % LW modified Ni‐YSZ; this suggested that the addition of LW affected the Ni particle distributions in the anode, which might influence the catalytic activity of fuel electro‐oxidation and reforming reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Although the addition of LW reduced the specific surface area of the anode, LW showed a better stabilizing effect than that of WO 3 because the specific surface area was almost unchanged after the reoxidation processes, whereas the surface areas of Ni‐YSZ and Ni‐YSZ‐0.42 wt % WO 3 decreased by 53 and 40 %, respectively, after the redox treatment. The elemental contents of the sample surfaces can be semiquantitatively measured by X‐ray photoelectron spectroscopy (XPS) . As shown in Table S1 in the Supporting Information, the atomic ratios of Ni metal were 56.3, 45.0, and 34.0 % for unmodified and 2 and 5 wt % LW modified Ni‐YSZ; this suggested that the addition of LW affected the Ni particle distributions in the anode, which might influence the catalytic activity of fuel electro‐oxidation and reforming reactions.…”
Section: Resultsmentioning
confidence: 99%
“…[184] Chemically, the diffusion of elements between materials in contact can lead to the formation of new phases and defects in a zone near the interface, which might result in property degradation of the layered system, as shown, for example, in the case of gadolinium-doped ceria in contact with YSZ. [185] Grain growth in YSZ mainly occurs during the final stage of sintering and is strongly dependent on the level of yttrium doping. Grain-boundary mobility in tetragonal zirconia (e.g., 2Y-TZP) is primarily controlled by the space charge segregation of cation solute, and second, by its diffusivity in the lattice.…”
Section: Sinteringmentioning
confidence: 99%
“…[ 184 ] Chemically, the diffusion of elements between materials in contact can lead to the formation of new phases and defects in a zone near the interface, which might result in property degradation of the layered system, as shown, for example, in the case of gadolinium‐doped ceria in contact with YSZ. [ 185 ]…”
Section: Wet Processing Of Zirconia Filmsmentioning
confidence: 99%
“…[47,48] We recently demonstrated that integrating a NiO-GDC anode into the standard fabrication route of an anode-supported fuel cell with 8YSZ electrolyte leads to a significant loss (> 50%) of performance in cell tests, and explored possible explanations due to interdiffusion between the GDC in the anode and the 8YSZ electrolyte, mainly measured on powder mixtures. [49] Here, we apply impedance analysis of the ionic conductivity of the actual cell to quantify the effect of the interdiffusion on the ionic conductivity of the electrolyte. Figure 8 a) shows a SEM cross-section of the fractured cell after testing, with a yellow line indicating the location of the EDX line scan shown in Figure 8 b).…”
Section: Interdiffusion Between Ysz and Gdc During Sinteringmentioning
confidence: 99%
“…In contrast, the interdiffusion zone at the interface to the GDC anode is approximately 6 µm thick (dashed black box in Figure 8 b)), and a substantial amount of Ce can be found in the electrolyte, which can be explained by the high co-sintering temperature during cell manufacturing (1400 °C) and the presence of NiO in the anode, which has been shown to accelerate the interdiffusion of 8YSZ and GDC. [49] This amount of interdiffusion can be assumed to decrease the ionic conductivity of the electrolyte. [49][50][51] In order to quantify the decrease of ionic conductivity and the mechanism behind it, we performed impedance analysis on the cell after it had been tested at SOFC temperatures.…”
Section: Interdiffusion Between Ysz and Gdc During Sinteringmentioning
confidence: 99%